Reference-Frame-Independent Measurement-Device-Independent Quantum Key Distribution With Modified Coherent States - Chun-Mei Zhang; Jian-Rong Zhu; Qin Wang (IEEE Photonics Journal)
We propose to implement reference-frame-independent measurement-device-independent quantum key distribution (RFI-MDI-QKD) with modified coherent states (MCS), and give the universal analytical formulas of three-intensity decoy-state RFI-MDI-QKD with MCS. Our simulation results indicate that compared with the widely used weak coherent states, MCS can improve significantly both the secret key rate and secure transmission distance of RFI-MDI-QKD, which is mainly attributed to the elimination of certain multi-photon events through the quantum interference effect in MCS.